Humidity-induced porous poly(lactic acid) membrane with enhanced flux for oil–water separation. Issue 5 (July 2019) - Liu, Zhi; Zhao, Jianghui; Li, Wei; Xing, Jian; Xu, Lan; He, Jihuan
Biodegradable and efficient filtration membrane is essential to practical oil–water separation. Herein, we fabricated highly porous membrane induced by the humidity. The resulting poly(lactic acid) fiber membrane exhibits superhydrophobicity due to more trapped air by the increased roughness of fiber at the relative humidity of 80%. Meanwhile, the increased humidity favors to the membrane porosity improvement from 81 ± 3.3% to 92 ± 4.1% with the humidity change from 40% to 80%. The superhydrophobicity company with the increased membrane porosity makes the functional poly(lactic acid) membrane with enhanced flux for practical oil–water separation.